On Capturing Oil Rents with a National Excise Tax Revisited - Santiago J. Rubio (Fondazione Eni Enrico Mattei (FEEM), 2004)
In this paper the scope of Bergstrom's (1982) results is studied. Moreover, his analysis is extended assuming that extraction cost is directly related to accumulated extractions. For the case of a competitive market it is found that the optimal policy is a constant tariff if extraction is costless. However, with depletion effects, the optimal tariff must ultimately be decreasing. For the case of a monopolistic market the results depend crucially on the kind of strategies the importing country governments can play and on whether the monopolist chooses the price or extraction rate. For a price-setting monopolist it is shown that the importing countries cannot use a tariff to capture monopoly rents if they are constrained to use open-loop strategies, even if the governments sign a tariff agreement. This result is drastically modified if the importing countries in the tariff agreement use Markov (feedback) strategies. For a quantity-setting monopolist the nature of the game changes and the importing country governments find it advantageous to set a tariff on resource importations. Moreover, in this case the importing countries in a tariff agreement enjoy a strategic advantage which allows them to behave as a leader.
Keywords: C73; D41; D42; F02; H20; Q38; 330; Tariffs; Tariff agreements; Non renewable resources; Depletion effects; Price-setting monopolist; Quantity-setting monopolist; Differential games; Open-loop strategies; Linear strategies; Markov-perfect Nash equilibrium; Markov-perfect Stackelberg equilibrium; Rententheorie; Erdölgewinnung; Zoll; Verbrauchsteuer; Monopol; Nash-Gleichgewicht; Theorie